Teaching English Pronunciation in Between Color and Vowel - Prisna Aswarita Putri; Fatima; Nurfauziah Mansur; Zul Aini Rengur; Zulfikri (Samudra Publisher, 2024)
Potent pronunciation is crucial for successful communication in any language, particularly in English, which presents numerous phonetic challenges for learners. Mastery of pronunciation not only enhances intelligibility but also fosters confidence among learners when engaging with native speakers. As educational methodologies evolve, innovative approaches to teaching pronunciation have emerged, one of which is the Color Vowel Approach. This research investigates the effectiveness of this method in enhancing English vowels pronunciation skills among first semester students of English Tadris study program in State Islamic University Datokarama Palu. With participants amounted to 40 students, this quasi- experimental research unveiled notable enhancement following the employment of Color Vowel Approach, backed by statistical findings (p<0.05). While the Color Vowel Approach provides thrilling learning atmosphere, more research is needed to fully understand its long-term effectiveness compared to other traditional method of teaching pronunciation. This research supplies to the discourse on the innovative teaching approach, offering practical recommendation in enhancing pronunciation skills in higher education.